Applying Systems thinking for Cyber Security Risk Management as part of Enterprise Risk Management Program for Stock and Derivatives Exchanges and Designated Clearing Organizations - Jayabalan, Harish (Digital Repository of Theses - SSBM Geneva, 2025)
Applying Systems thinking for Cyber Security Risk Management as part of Enterprise Risk Management Program for Stock/Derivatives Exchanges and Designated Clearing Organizations>